(untitled) (Applied Biological Research, 2024)
The probiotics, when administered in adequate amounts, have the ability to confer health benefits to the host by positively influencing the composition and function of gut microbiota. The present study was aimed to isolate and characterize the probiotic bacteria from locally available curd and Yakult samples and compare them with Sporolac for probiotic properties. Three bacterial isolates were isolated and tentatively identified on morpho-cultural and biochemical characteristics as Lactobacillus sp. The isolates were named Lactobacillus sp. isolates PBC, PBY and SPO. E coli was used as negative control. The study revealed that the isolates exhibited auto-aggregation and co aggregation activities, more in isolate SPO as compared to the isolates PBC and PBY. Biofilm and quorum quenching activities were high in Lactobacillus sp. isolate PBC and PBY as compared to Lactobacillus sp. isolate SPO. The other tests showed more or less similar properties as compared to the commercially available product. The study revealed that the probiotic bacterial isolates from curd and Yakult had more beneficial properties than the commercially processed probiotic bacteria.